Clinical validity of a relocation stress scale for the families of patients transferred from intensive care units. Issue 13 (9th February 2015) - Oh, HyunSoo; Lee, Seul; Kim, JiSun; Lee, EunJu; Min, HyoNam; Cho, OkJa; Seo, WhaSook
<x xml:space="preserve">Abstract</x> Aims and objectives This study was conducted to develop a family relocation stress scale by modifying the Son's Relocation Stress Syndrome Scale, to examine its clinical validity and reliability and to confirm its suitability for measuring family relocation stress. Background The transfer of ICU patients to general wards is a significant anxiety‐producing event for family members. However, no relocation stress scale has been developed specifically for families. Design A nonexperimental, correlation design was adopted. Methods The study subjects were 95 family members of 95 ICU patients at a university hospital located in Incheon, South Korea. Face and construct validities of the devised family relocation stress scale were examined. Construct validity was examined using factor analysis and by using a nomological validity test. Reliability was also examined. Results Face and content validity of the scale were verified by confirming that its items adequately measured family relocation stress. Factor analysis yielded four components, and the total variance explained by these four components was 63·0%, which is acceptable. Nomological validity was well supported by significant relationships between relocation stress and degree of preparation for relocation, patient self‐care ability, family burden and satisfaction with the relocation process. The devised scale was also found to have good reliability. Conclusions The family relocation stress scale devised in this study was found to have good validity and reliability, and thus, is believed to offer a means of assessing family relocation stress. Relevance to clinical practice The findings of this study provide a reliable and valid assessment tool when nurses prepare families for patient transfer from an ICU to a ward setting, and may also provide useful information to those developing an intervention programme for family relocation stress management.